2012
DOI: 10.1002/ajmg.a.35390
|View full text |Cite
|
Sign up to set email alerts
|

XX male sex reversal with genital abnormalities associated with a de novo SOX3 gene duplication

Abstract: Differentiation of the bipotential gonad into testis is initiated by the Y chromosome-linked gene SRY (Sex-determining Region Y) through upregulation of its autosomal direct target gene SOX9 (Sry-related HMG box-containing gene 9). Sequence and chromosome homology studies have shown that SRY most probably evolved from SOX3, which in humans is located at Xq27.1. Mutations causing SOX3 loss-of-function do not affect the sex determination in mice or humans. However, transgenic mouse studies have shown that ectopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 27 publications
(38 reference statements)
1
49
0
Order By: Relevance
“…16 Interestingly, SOX3 duplications have been reported in two unrelated 46,XY individuals with X-linked hypopituitarism, whereas their carrier mothers were unaffected. 36,37 No hypopituitarism was present in our case 20 or in the patient reported by Moalem et al 17 An X-linked dominant but leaky mutation affecting sex development in a portion of XX subjects might be hypothesized, either as a consequence of the X-inactivation pattern in the developing gonad or of specific genomic modifiers.…”
Section: Sox3 Duplicationsupporting
confidence: 42%
See 2 more Smart Citations
“…16 Interestingly, SOX3 duplications have been reported in two unrelated 46,XY individuals with X-linked hypopituitarism, whereas their carrier mothers were unaffected. 36,37 No hypopituitarism was present in our case 20 or in the patient reported by Moalem et al 17 An X-linked dominant but leaky mutation affecting sex development in a portion of XX subjects might be hypothesized, either as a consequence of the X-inactivation pattern in the developing gonad or of specific genomic modifiers.…”
Section: Sox3 Duplicationsupporting
confidence: 42%
“…35 Duplications involving SOX3 and deletions of its 5′ region (Figure 1d) have been reported in at least four cases of XX DSD. 16,17 Moreover, a mouse model in which SOX3 is ectopically expressed in the developing gonads shows complete XX sex reversal, suggesting that gain-of-function mutations of SOX3 might act as an SRY surrogate in sex determination, promoting SOX9 gonadal expression. 16 Interestingly, SOX3 duplications have been reported in two unrelated 46,XY individuals with X-linked hypopituitarism, whereas their carrier mothers were unaffected.…”
Section: Sox3 Duplicationmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis has been strongly supported by recent studies of Sox3 transgenic mice and human sex reversal cases. Ectopic expression of Sox3 in the urogenital ridge of transgenic mice induces complete XX male sex reversal 8 , and rearrangements in the Sox3 regulatory region are associated with XX male sex reversal in human 8,41 , suggesting that Sry and Sox3 are functionally interchangeable in sex determination. Thus, although loss of Sox3 function does not affect sex determination 42 , certain gain-of-function mutations in Sox3 may result in XX male sex reversal in mouse and human by mimicking the function of Sry, supporting the notion that Sry .…”
Section: Discussionmentioning
confidence: 99%
“…vious studies have identified various heterozygous duplications involving SOX3 and/or its flanking regions in patients with 46,XX disorders of sex development (DSD) [Sutton et al, 2011;Moalem et al, 2012;Mizuno et al, 2014]. These duplications were predicted to induce ectopic expression of SOX3 in 46,XX gonads, which switches the developmental process toward testicular formation [Sutton et al, 2011].…”
mentioning
confidence: 99%